“Socio-Economics of Portuguese Cod Fisheries: Past, Present and Perspectives for the Future” - COELHO, MANUEL (2011)
Property rights are in the center of fisheries management difficulties. Portuguese cod fisheries give good examples of this kind of management problems. This paper studies the socio-economic impacts of the institutional change of cod fisheries framework in Portugal and asks for the perspectives of future development of this segment of Portuguese fisheries. In one decade (from 1976 to 1986) this segment of the Portuguese fisheries had to face two essential restrictions to the development of fishing activities: the new regime of the 200 miles and the adhesion to European Community with the consequent integration in the Common Fisheries Policy. After a profound downsizing process we are still confronted with an overcapacity problem. The possible enlargement of Economic Exclusive Zones and the rehabilitation of the Continental Platform statute constitute the main change that severely can affect the future of these fisheries.